Peningkatan Kompetensi SDM UMKM di Kota Depok Melalui Program Pendampingan Usaha - Adi Martono; Vivi Iswanti Nursyirwan; Edon Ramdani (Universitas Pamulang, 2021)
The implementation of community service with MSMEs in the city of Depok is motivated by the need to increase the capacity and ability of MSMEs in terms of HR competence. The training provided to MSMEs is more on product development and marketing. Whereas the ability of SMEs in managing human resources will have an impact on the ability of these SMEs to improve their business performance and grow sustainably. Related to this, training was held for MSMEs in the city of Depok which was the implementation of community service initiated by the lecturers of the Accounting S1 Study Program, Faculty of Economics and Business, Pamulang University in collaboration with the Department of Cooperatives and Micro Enterprises of the Depok City Government. The purpose of this Community Service activity is not only as an implementation of the implementation of the Tri Dharma of Higher Education, it is also a solution to the problems faced by MSMEs in managing human resources. The method of implementing this Community Service is in the form of training in the form of HR competency-based business assistance, covering the knowledge, skills and attitudes of 25 MSMEs from the city of Depok. The results of the implementation of this activity are in the form of post-test results which were held before and after the training. These results indicate an increase in participants' knowledge by an average of 3% from the initial pre-test value. The conclusion of this activity is that the training provided to MSME actors in the city of Depok needs to be optimized so that the results obtained are as expected. As a suggestion, the mentoring program for MSMEs in the city of Depok should be carried out on an ongoing basis so that it can be evaluated periodically and with more diverse training topics and involves experienced practitioners